USING SHORT STORY IN IMPROVING STUDENTS’ VERBAL VOCABULARY MASTERY - Sulaeha, Sulaeha; Kamsinah, Kamsinah; Annur, Muhammad Jabal (English Language Teaching for EFL Learners Journal, 2020)
This research aims at finding out the effectiveness of using short storyin improving students’ verbal vocabulary mastery. The subject of the research was the second grade students of SMAN 2 Bulukumba. In collecting the data, this research used pre-test and post-test. The type of this research was quantitative with quasi-experimental design. It was applied with two group’s pre-test and post-test design. The population of this study is 215 students from the second grade students of SMAN 2 Bulukumba. This study is quantitative research with quasi experimental design by using 27 students in control class and 30 students in experimental class. This is proved by figure of means group, the standard deviation and value of t-test which revealed that the mean score of experimental group is higher than the mean score of control group. The result in t-test of experimental class is higher than t-table. It showed that t-table 1, 25>t-table at significance level 2,0 and 12,89> 2.045 t-table at 0,05 (98%). It means that using short story was more effective in improving students’ verbal vocabulary mastery at the second grade students of SMAN 2 Bulukumba.